A PCE-based rheology modifier allows machining of solid cast green bodies of alumina. Issue 3 (15th February 2016) - Avci, Gokay; Akhlaghi, Omid; Ustbas, Burcin; Ozbay, Ceren; Menceloglu, Yusuf Z.; Akbulut, Ozge
Abstract: The performance of a poly(carboxylate ether) (PCE)-based superplasticizer to enable the machining of green bodies that are solid cast from suspensions of alumina was investigated. An alumina loading of 35 vol% in the presence of 1.25 wt% superplasticizer was established to be suitable for lathing and removal of significant amount of material through drilling. A reduction of 77% in the diameter of green bodies that corresponds to a 59% reduction in volume was achieved. The lathed green bodies exhibited smooth terraces without visible cracks. All of the green bodies were sintered without a polymer burnout step.